Übergänge von Maßnahmen der Berufsvorbereitung in Ausbildung und weiterführende Schulen zu Zeiten eines günstigen Ausbildungsstellenmarkts : Deskription und Erklärungsansätze - Nickolaus, Reinhold [Verfasser]; Behrendt, Stefan [Verfasser]; Gauch, Sabine [Verfasser]; Windaus, Anne [Verfasser]; Seeber, Susan [Verfasser] (My University, 2018)
"Im vorgelegten Beitrag werden auf Basis einer längsschnittlichen Untersuchung, bezogen auf ein Bundesland die Übergänge aus dem Übergangssystem unter anderem unter Berücksichtigung von Leistungen in den Basiskompetenzen analysiert. Des Weiteren werden partiell Vergleiche mit Übergängen in anderen Bundesländern und für Zeiten mit einem angespannteren Ausbildungsstellenmarkt vorgenommen. Dabei wird deutlich, dass nach wie vor erhebliche Anteile der Jugendlichen erneut in eine Übergangsmaßnahme einmünden und für den Übergang in eine vollqualifizierende Ausbildung vor allem die 'Kopfnoten', die Praktikumsqualität, der Migrationshintergrund und mit besonderem Gewicht Mehrfachschleifen im Übergangsystem bedeutsam werden. Die Leistungen in den Basiskompetenzen werden weder in Form von Testleistungen noch in Form von Noten prädiktiv. Für den Übergang in weiterführende Schulen sind die Leistungen in den Basiskompetenzen hingegen bedeutsam. Insgesamt ergibt sich für den Übergang in weiterführende Schulen ein völlig anderes Erklärungsmodell." (Autorenreferat ; BIBB-Doku)

"In this article we discuss the development of young people in different prevocational programs in Baden-Württemberg. We refer the study to encompasses three measurement points. At the beginning and at the end of the prevocational education and training standardized tests were used to measure the development in basic competencies, e. g. mathematics and reading. The social, cultural and family background as well as some information about the transition process were surveyed with a student questionnaire. At the third occasion of measurement, a follow up telephone interview conducted three to six month after the training accomplished. The research objective lies on the transition process, like the integration into an apprenticeship, into the labor market or another educational program. In contrast to the assumptions that the students enter into an apprenticeship after the prevocational program has been finished, this study shows that the majority of students are entering into another prevocational program. The most important factors for a successful transition into an apprenticeship are on the one hand a completed internship during the prevocational program and positive comments regarding behavior and attitudes to learning and work in the students’ reports. On the other hand, a migration background and the repeated participation in a prevocational program could limit a successful transition into the dual system, but not for full-time school based vocational training. Contrary to the expectation with regard to other research results, basic competencies in math and reading or marks do not influence the success in finding an apprenticeship place." (author's abstract)
Transitions between vocational preparation and initial vocational training or further schooling
Keywords: G 1.3.2.2 Übergänge; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; S 1.2 Berufsvorbereitung; I 2.1.2.4 Baden-Württemberg; Übergangssystem; Berufseinmündung; Erste Schwelle; Grundbildung; Weiterführende Schule; Baden-Württemberg